2013
DOI: 10.2147/bctt.s47172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CYP2D6 and UGT2B7 polymorphisms on pharmacokinetics of tamoxifen in Thai breast cancer patients

Abstract: PurposeThe objective of this study was to evaluate the impact of CYP2D6 and UGT2B7 polymorphisms on tamoxifen (TAM) pharmacokinetics in Thai breast cancer patients.MethodsThai female breast cancer patients treated with TAM were included in the study. Patients were genotyped for CYP2D6 and UGT2B7 polymorphism, and plasma levels of TAM and its potent active metabolite endoxifen (END), at steady state, were identified.ResultsFifty-nine female breast cancer patients were included in the study. The average age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 20 publications
(33 reference statements)
1
18
2
Order By: Relevance
“… 33 35 The prevalence of UGT1A1 * 6 , which is more commonly observed in Asian populations and absent among Caucasians, resembled earlier studies that reported a frequency of 9%. 36 A previous study of UGT2B7 * 2 among Thai patients with breast cancer reported an allele frequency of 28%, 37 which is similar to the 31.5% reported in this study. CYP1A2 * 1F was associated with an increased risk of cholangiocarcinoma (CCA), while NAT2 * 6 and * 7 were associated with a lower risk of CCA in a study by Prawan et al, 38 who evaluated the relationship between CYP1A2 and NAT2 alleles and CCA among individuals living in the northeastern region of Thailand.…”
Section: Discussionsupporting
confidence: 86%
“… 33 35 The prevalence of UGT1A1 * 6 , which is more commonly observed in Asian populations and absent among Caucasians, resembled earlier studies that reported a frequency of 9%. 36 A previous study of UGT2B7 * 2 among Thai patients with breast cancer reported an allele frequency of 28%, 37 which is similar to the 31.5% reported in this study. CYP1A2 * 1F was associated with an increased risk of cholangiocarcinoma (CCA), while NAT2 * 6 and * 7 were associated with a lower risk of CCA in a study by Prawan et al, 38 who evaluated the relationship between CYP1A2 and NAT2 alleles and CCA among individuals living in the northeastern region of Thailand.…”
Section: Discussionsupporting
confidence: 86%
“… 30 CYP2D6*10 /* 10 , a common reduced-activity allele in Asians including Thais, was demonstrated to be associated with significantly lower endoxifen level compared to CYP2D6*1 /* 1 at steady-state of tamoxifen adjuvant therapy. 8 , 31 , 32 Consequently, Asian women carrying CYP2D6*10/*10 genotype had significantly shorter DFS than those who carry CYP2D6*1/*1 genotype treated with the equivalent dose of tamoxifen. 6 , 7 , 10 , 31 Furthermore, CYP2D6*10/*10 was independently correlated to unfavorable outcomes in tamoxifen treatment, significant in the multivariate analyses adjusted for clinical prognostic factors.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence and type of incomplete functional allele (null allele and reduced allele) that is involved in CYP450 enzyme activity are different in different populations;14 the prevalence of CYP2D6*4 (null allele) has been found to be higher in Caucasians15 than in Asians16 or Thais,17 while that of CYP2D6*10 (reduced allele) has been found to be higher in Asians,16 including Thais,18 than in Caucasians15 and CYP3A5*3 (null allele) is the major allele in Caucasians15 and Asians,16 including Thais 18. Previous research has suggested that the low activities of CYP2D6 and CYP3A5 enzymes account for 25%–55% and 40%–50% of the polymorphisms, respectively, in Thai breast cancer patients 17–19. Early researches suggested that CYP2D6*10/*10 patients had shorter disease-free survival than heterozygous CYP2D6*10 ( p =0.046)17 and lower END concentrations than those patients with CYP2D6*1/*10 and CYP2D6*1/*1 ( p =0.045)19 among Thai breast cancer patients; however, the result was not completely generalized to target population because of the limited sample size 19.…”
Section: Introductionmentioning
confidence: 99%